Synthesis and characterization of 18F‐labeled active site inhibited factor VII (ASIS). (27th March 2015) - Erlandsson, Maria; Nielsen, Carsten H.; Jeppesen, Troels E.; Kristensen, Jesper B.; Petersen, Lars C.; Madsen, Jacob; Kjær, Andreas
<x xml:space="preserve">Abstract</x> Activated factor VII blocked in the active site with Phe–Phe–Arg–chloromethyl ketone (active site inhibited factor VII (ASIS)) is a 50‐kDa protein that binds with high affinity to its receptor, tissue factor (TF). TF is a transmembrane glycoprotein that plays an important role in, for example, thrombosis, metastasis, tumor growth, and tumor angiogenesis. The aim of this study was to develop an 18F‐labeled ASIS derivative to assess TF expression in tumors. Active site inhibited factor VII was labeled using N‐succinimidyl‐4‐[18F]fluorobenzoate, and the [18F]ASIS was purified on a PD‐10 desalting column. The radiochemical yield was 25 ± 6%, the radiochemical purity was >97%, and the pseudospecific radioactivity was 35 ± 9 GBq/µmol. The binding efficacy was evaluated in pull‐down experiments, which monitored the binding of unlabeled ASIS and [18F]ASIS to TF and to a specific anti‐factor VII antibody (F1A2‐mAb). No significant difference in binding efficacy between [18F]ASIS and ASIS could be detected. Furthermore, [18F]ASIS was relatively stable in vitro and in vivo in mice. In conclusion, [18F]ASIS has for the first time been successfully synthesized as a possible positron emission tomography tracer to image TF expression levels. In vivo positron emission tomography studies to evaluate the full potential of [18F]ASIS are in progress.